Optimal prioritisation of asphalt pavement maintenance using gray realation analysis and cost-benefit analysis - Yan Zhang; Hao-Chang Li; Yu-Xin Zhang; Wen-Ke Zang; Kai-Wen Yao (Građevinar)
Pavement maintenance prioritisation, which considers both quality and cost, is an important decision-making problem. The common approach involves the prioritisation of road repairs with more extensive surface damages but this does not always align with the actual repair needs. To address this, a method based on the grey correlation theory was introduced to evaluate pavement performance. This method was employed to determine the optimal maintenance time for asphalt pavements. Once the sequence was established, the ideal maintenance schedule for the pre-maintenance sections was determined using a cost–benefit model. This evaluation method is particularly useful for quantitative analyses of the influences of pavement age and traffic volume on pavement performance parameters. The results demonstrate that grey relation sorting effectively weighs the factors and provides rankings for road segments requiring maintenance. A cost–benefit analysis model was used to assess the maintenance sections. This model can guide decisions regarding pre-maintenance sections and assess pavement conditions, thus resulting in outcomes that align better with real-world situations and human judgment. These findings are expected to be valuable for the long-term maintenance of asphalt pavements.